2012
DOI: 10.1111/j.1365-2834.2012.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Part 2: Nurses' career aspirations to management roles: qualitative findings from a national study of Canadian nurses

Abstract: Leaders need to ensure that they convey positive images of manager roles and actively identify and support staff nurses with leadership potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
(31 reference statements)
4
22
0
Order By: Relevance
“…As expected in this study social support of their immediate supervisor influence nurses’ interest in management. This is in line with a study by Wong et al () where participants expressed that working with an effective manager stimulates interest in management roles. The JD‐R model suggests that different leadership styles will influence employees’ work motivation through job resources and job demands (Bakker & Demerouti, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As expected in this study social support of their immediate supervisor influence nurses’ interest in management. This is in line with a study by Wong et al () where participants expressed that working with an effective manager stimulates interest in management roles. The JD‐R model suggests that different leadership styles will influence employees’ work motivation through job resources and job demands (Bakker & Demerouti, ).…”
Section: Discussionsupporting
confidence: 91%
“…This study and earlier research (Laschinger et al, ; Wong et al, ) show that it is still the youngest nurses who report greater interest in pursuing management roles. Older nurses may have made a well thought‐through decision about their career.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…3 Charge nurses cite several barriers to their pursuit of nurse manager roles, according to Sherman, including concerns about role qualification, such as a lack of education and leadership experience, and the self-confidence needed to lead. According to a recent Canadian study, only 19% of surveyed staff nurses expressed interest in management roles, citing concerns such as the need for additional clinical experience and education, less time spent with patients, a potentially heavier work load, and worklife imbalance.…”
Section: Obstacles To Leadershipmentioning
confidence: 99%
“…Since then, interest in leadership across the profession has grown alongside an emerging evidence base demonstrating its importance in tackling the key challenges of work satisfaction, patient outcome, recruitment and retention of nursing staff. A recent systematic review on the nature of nurse leadership revealed a strong connection between a relational approach to leadership and good patient outcomes (Wong et al, ). Identification of fundamental factors related to these principal dilemmas has shown that management behaviours and leadership styles are strongly related to staff members’ intentions to leave or stay in the organization (Force, ).…”
Section: Introductionmentioning
confidence: 99%